2021
DOI: 10.1371/journal.ppat.1009217
|View full text |Cite
|
Sign up to set email alerts
|

EBV miRNAs are potent effectors of tumor cell transcriptome remodeling in promoting immune escape

Abstract: The Epstein Barr virus (EBV) contributes to the tumor phenotype through a limited set of primarily non-coding viral RNAs, including 31 mature miRNAs. Here we investigated the impact of EBV miRNAs on remodeling the tumor cell transcriptome. Strikingly, EBV miRNAs displayed exceptionally abundant expression in primary EBV-associated Burkitt’s Lymphomas (BLs) and Gastric Carcinomas (GCs). To investigate viral miRNA targeting, we used the high-resolution approach, CLASH in GC and BL cell models. Affinity constant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 105 publications
0
21
0
Order By: Relevance
“…Targets of EBV miRNAs were also shown to be enriched for genes with functions in innate and adaptive immune responses [219]. Moreover, the increased levels of the EBV miRNA correlated with reduced immune cell infiltration in both BL and GC [219]. It is noteworthy that this same study showed that EBV miRNAs form thermodynamically stable complexes with their targets at a higher efficacy than cellular miRNAs, indicating that they are likely to override any regulation of immune targets by cellular miRNA [219].…”
Section: Role Of Ncrna In Immune Evasionmentioning
confidence: 78%
See 1 more Smart Citation
“…Targets of EBV miRNAs were also shown to be enriched for genes with functions in innate and adaptive immune responses [219]. Moreover, the increased levels of the EBV miRNA correlated with reduced immune cell infiltration in both BL and GC [219]. It is noteworthy that this same study showed that EBV miRNAs form thermodynamically stable complexes with their targets at a higher efficacy than cellular miRNAs, indicating that they are likely to override any regulation of immune targets by cellular miRNA [219].…”
Section: Role Of Ncrna In Immune Evasionmentioning
confidence: 78%
“…In nasal NK cell lymphoma, BART20-5p and BART8 suppress IFN-γ-STAT1 signaling [218]. Targets of EBV miRNAs were also shown to be enriched for genes with functions in innate and adaptive immune responses [219]. Moreover, the increased levels of the EBV miRNA correlated with reduced immune cell infiltration in both BL and GC [219].…”
Section: Role Of Ncrna In Immune Evasionmentioning
confidence: 99%
“…In addition, miR-BART6-3p regulates the expression of the IL-6 receptor ( IL-6R ), being able to contribute to immune system evasion [ 94 ]. Furthermore, it has been postulated that EBV-miRNAs have a role in the microenvironment regulation, reducing the innate and adaptative immune response in EBV-positive tumors, similar to BL ( Figure 2 ) [ 96 ].…”
Section: Implications Of Epstein–barr Virus In the Different Hiv-related Lymphoma Typesmentioning
confidence: 99%
“…S4 ) of the top 10 miRNA-targeted genes, Toll receptor signaling pathway and CCKR signaling pathway maps are the top 2 pathways that can be potentially regulated by circ LMP-2_e5 through miRNA sponging. However, a search for potential AGO2: miRNA: circ LMP2-e5 interactions via interrogating publicly available AGO2 pulldown assay datasets from EBV-positive cell lines of different cell types and latencies 40 43 did not reveal clear such interaction (data not shown). We note that these datasets only encompass the latent state, hence there is still a possibility of circ LMP2-e5 functioning as a miRNA sponge during the lytic state.…”
Section: Discussionmentioning
confidence: 99%